Pengaruh Penambahan Zat Aditif Sika Viscocrete Terhadap Kuat Tekan Mutu Beton K-300 Umur 14 Hari - R.R. Susi Riwayati; Roby Habibi (Jurnal Tekno Global, 2021)
Research on concrete which is ongoing at this time aims to obtain good quality and high quality concrete, to get it it needs to be mixed with additives (Admixture) as an added material for concrete mixtures. Sika Viscocrete is an added material that can help concrete improve its performance at a faster time and has the dual function of reducing the amount of water mixing required to produce concrete with a certain consistency and speed up the bonding of the concrete. The purpose of this study was to determine the effect of adding the additive ViscoCrete sika to the compressive strength of the K-300 concrete. The sample used was 15cm x 15cm x 15cm cuboid at the age of 14 days. With variations, namely Normal Concrete and Normal Concrete + Sika Viscocrete 1%, 2%, 3% with 9 samples in each variation. The results showed that the value of the compressive strength of concrete with the addition of 2% Sika Viscocrete-3115N aged 14 days to normal concrete was 315, 07 Kg / Cm2. While the addition of 3% Sika Viscocrete-3115N obtained the optimum value at the age of 14 days of 358.13 Kg / Cm2. Kata Kunci : K-300 Concrete, Additives, Viscocrete Sika and Concrete Presure